(untitled) (Revista LIDER, 2020)
In recent decades, citizen participation has become an integrated part of government housing and urban planning in Chile. As a result, the “I love my Neighborhood” program was created in 2006 (PQMB), aimed at improving the quality of life of the inhabitants of socially vulnerable neighborhoods by means of a participative process. This paper examines the participation implemented by the PQMB in the commune of Valparaíso. To this end, a qualitative case study methodology was used in the neighborhoods of Rodelillo and Porvenir Bajo, where semistructured interviews were conducted with community leaders. The results of the interview suggest that citizen participation facilitated through the PQMB consisted in the delivery of consultation and information mechanisms. Similarly, obstacles are observed, such as exclusive leaderships and a new communication process among the neighbors.